Penggunaan Dan Fungsi Saluang Panjang Di Nagari Ujuang Jalan Kecamatan Alam Pauah Duo Kabupaten Solok Selatan - Jovi Kurniawan; Marzam Marzam (FBS Universitas Negeri Padang, 2020)
The purpose of this study is to express and describe the usage and function of Saluang Panjang in Nagari Ujuang Jalan Alam Pauah Duo District, Solok Selatan Regency. Type of this research was qualitative study with using descriptive analysis method. The main instrument in this study was the researcher. The additional instruments used supporting instruments such as stationery, photo camera and camcorder. Type of data used primary and secondary data. Technqiues ofdata collection were carried out by taking observation, interview and documentation. The steps in analyzing data were done by collecting, describing and making conclusion of data. The results show that Saluang Panjang can still be found and displayed on various occasions and events. Saluang Panjang is only used as an entertainment but now it has developed into a musical accompaniment to randai dance. The existence of Saluang Panjang in Nagari Ujuang Jalan Alam Pauah Duo District, Solok Selatan Regencyis not only limited to traditional arts used in various events, but of course it has its own meaning or function for the society in Nagari Ujuang Jalan Alam Pauah Duo District, Solok Selatan Regency. Saluang Panjang contains various values and norms that are useful as a way of life in society. The values of the norm are contained in various Dendang dendang and the rules in the art.